A Simple Risk Scoring Systems to evaluate the presence of aneurysm and one-year mortality in patients with abdominal aortic aneurysm using CHA2DS2-VASc and ATRIA - Aksoy,Fatih (2021)
SUMMARY OBJECTIVE: We aimed to demonstrate the clinical utility of CHA2DS2-VASc and anticoagulation and risk factors in atrial fibrillation risk scores in the assessment of one year mortality in patients with abdominal aortic aneurysm. METHODS: We designed a retrospective cohort study using data from Suleyman Demirel University Hospital for the diagnosis of abdominal aortic aneurysm. The study included 120 patients with abdominal aortic aneurysm who underwent aortic computed tomography. Patients were divided into two groups according to presence of abdominal aortic aneurysm and the development of mortality. Predictors of mortality were determined by multiple logistic regression analysis. RESULTS: Multivariate regression analysis showed that CHA2DS2-VASc score, advanced age, female gender and elevated white blood cell counts were independent predictors of abdominal aortic aneurysm development while CHA2DS2-VASc score and elevated glucose levels were independent predictors of one year mortality in patients with abdominal aortic aneurysm. The concordance statistics for anticoagulation and risk factors in atrial fibrillation risk Score and CHA2DS2-VASc risk score respectively were 0.96 and 0.97 and could significantly predict one year mortality in patients with abdominal aortic aneurysm (p<0.001, and p<0.001, respectively). CONCLUSIONS: CHA2DS2-VASc and anticoagulation and risk factors in atrial fibrillation risk scores are easily obtained in an emergency setting and can accurately predict one year mortality as a noninvasive follow-up in patients with abdominal aortic aneurysm. These simple scores could be used as a point of care decision aid to help the clinician in counseling patients presenting with abdominal aortic aneurysm and their families on treatment protocols.